Characterizing Changes in Geometry and Flow Speeds of Land- and Lake-Terminating Glaciers at the Headwaters of Yarlung Zangbo River, Western Himalayas - Min Zhou; Yuzhe Wang; Tong Zhang; Weijun Sun; Yetang Wang (Remote Sensing)
The glaciers of the Himalayas are essential for water resources in South Asia and the Qinghai–Tibet Plateau, but they are undergoing accelerated mass loss, posing risks to water security and increasing glacial hazards. This study examines long-term changes in the geometry and flow speeds of both land- and lake-terminating glaciers at the headwaters of the Yarlung Zangbo River, using field measurements, remote sensing, and numerical ice flow modeling. We observed significant heterogeneity in glacier behaviors across the region, with notable differences between glacier terminus types and even among neighboring glaciers of the same type. Between 1974 and 2020, glacier thinning and mass loss rates doubled in the early 21st century (<semantics>−0.57±0.05</semantics> m w.e. a−1) compared to 1974–2000 (<semantics>−0.24±0.11</semantics> m w.e. a−1). While lake-terminating glaciers generally experienced more rapid retreat and mass loss, the land-terminating N241 Glacier displayed comparable mass loss rates. Lake-terminating glaciers retreated by over 1000 m between 1990 and 2019, while land-terminating glaciers retreated by less than 750 m. The ITS_LIVE velocity dataset showed higher and more variable flow speeds in lake-terminating glaciers. Numerical modeling from 2000 to 2017 revealed divergent changes in flow regimes, with lake-terminating glaciers generally experiencing acceleration, while land-terminating glaciers showed either a slowing down or stable flow behavior. Our findings underscore the significant role of lake-terminating glaciers in contributing to ice mass loss, emphasizing the need for advanced glacier models that incorporate dynamic processes such as frontal calving and longitudinal coupling.